2018
DOI: 10.1111/apa.14463
|View full text |Cite
|
Sign up to set email alerts
|

No neurodevelopmental benefit of cerebral oximetry in the first randomised trial (SafeBoosC II) in preterm infants during the first days of life

Abstract: Cerebral NIRS monitoring was not associated with long-term benefits or harm with regard to neurodevelopmental outcome at two years of corrected age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…The trial showed significantly better cranial ultrasound severity scores in the treatment group than the control group in early scans and at term equivalent age. However, there was no significant difference in overall cranial ultrasound scores, MRI findings, early electroencephalography, blood biomarkers of brain injury or neurodevelopmental outcomes between their two trial groups 21–23. Our study highlights the possibility that the threshold of 55% is not applicable to all study populations.…”
Section: Discussionmentioning
confidence: 66%
“…The trial showed significantly better cranial ultrasound severity scores in the treatment group than the control group in early scans and at term equivalent age. However, there was no significant difference in overall cranial ultrasound scores, MRI findings, early electroencephalography, blood biomarkers of brain injury or neurodevelopmental outcomes between their two trial groups 21–23. Our study highlights the possibility that the threshold of 55% is not applicable to all study populations.…”
Section: Discussionmentioning
confidence: 66%
“…In a 2011 review article, Greisen et al estimated that a trial with sufficient power to detect a 20% reduction of the incidence of brain injury in extreme premature neonates should recruit about 4000 patients . A recent international phase II feasibility randomized clinical trial in 160 extremely preterm infants showed a reduction in cerebral hypoxic events due to a NIRS‐guided treatment protocol but failed to detect any effect on the occurrence of early biomarkers of brain injury or EEG burst rates and neurodevelopmental outcome at 2 years of age . In this neonatal ICU trial, only one intervention to normalize c‐rSO 2 values was allowed at a time and the patient was re‐assessed 30‐60 minutes later.…”
Section: A Practical Introduction To Near‐infrared Spectroscopy (Nirs)mentioning
confidence: 94%
“…60 A recent international phase II feasibility randomized clinical trial in 160 extremely preterm infants showed a reduction in cerebral hypoxic events due to a NIRS-guided treatment protocol 56 but failed to detect any effect on the occurrence of early biomarkers of brain injury or EEG burst rates 61 and neurodevelopmental outcome at 2 years of age. 62 In this neonatal ICU trial, only one intervention to normalize c-rSO 2 values was allowed at a time and the patient was re-assessed 30-60 minutes later. Transient anticipated changes in c-rSO 2 values due to routine interventions (ie, endotracheal tube suctioning) were not listed in the treatment protocol.…”
Section: Nirs and Patient Outcomementioning
confidence: 99%
“…A recent multi‐center clinical trial assessed ability of cerebral oximeters to impact preterm intensive care. The trial demonstrated that informing care with oximetry could reduce the burden of hypoxia but did not see any link between outcome of patients and oximetry (Plomgaard et al., 2019). International efforts to establish optical monitoring techniques in the NICU should be used as an example for the introduction and acceptance of newer techniques (such as those described in Section 3).…”
Section: Neurological Monitoring: Current Statusmentioning
confidence: 99%